CHRONIC MYELOPROLIFERATIVE NEOPLASMS: A COLLABORATIVE APPROACH - Lisa Pieri; Paola Guglielmelli; Alessandro Maria Vannucchi (Mediterranean Journal of Hematology and Infectious Diseases)
The classic chronic myeloproliferative neoplasms (MPN) include different entities that pose significant challenges for their optimal diagnosis, treatment and overall management. Polycythemia Vera and Essential Thrombocythemia are the most common among chronic myeloproliferative neoplasms (MPNs); major causes of morbidity and mortality are represented by arterial and venous thrombosis, as well as evolution to myelofibrosis or transformation to acute leukemia. However, survival is only minimally affected. Therapy aims at reducing the rate of thrombosis without increasing the risk of hematologic transformation which could be caused by exposure to cytotoxic drugs. On the other hand, survival is significantly reduced in primary myelofibrosis, and the clinical manifestations may be disabling. In the absence of therapies with the potential of curing the disease, a careful risk-oriented approach is employed for stratifying patients to the most appropriate, currently available, therapeutic options. In this brief review, we will discuss some of the key issues that can arise along the clinical course of MPNs and require an integrated, strictly patient-oriented, approach.